High-frequency in vitro shoot regeneration of Saintpaulia ionantha Wendl. by light-emitting diodes - Bien, Le The; Thanh Tung, Hoang; Dac Khai, Hoang; Manh Cuong, Do; Luan, Vu Quoc; Ba Nam, Nguyen; Thi Huong, Trinh; The Vinh, Bui Van; Nhut, Duong Tan (Vietnam Journal of Biotechnology, 2021)
Saintpaulia ionantha Wendl. is a small flower, with a variety of colors, which are commonly grown indoors for decorative purposes. Currently, micropropagation of S. ionantha has been achieved certain results; however, the shoot quality as well as number of shoots regeneration was not high. In this study, the effect of LEDs system on the shoot multiplication and shoot quality of S. ionantha was conducted. The leaves were cut into square patterns without the main veins (1 cm × 1 cm), and the petiole (3 mm in diameter) was cut with a thick layer (2 mm) of longitudinal cell (lTCL), which were used as the initial materials. The explants were placed under LEDs conditions; and white fluorescent tube lamp (FL) was used as the control for shoot regeneration and rooting. The results found that the quality of light affects the regeneration, growth and development of S. ionantha shoots. The LED condition with a combination of 7R + 3B are optimal for high-frequency of shoot regeneration with the regeneration rate: 67.25%, and number of shoots: 9.33 shoots/explant from the leaves without the main veins. The higher shoot multiplication (number of shoots: 10.00 shoots/explant, fresh weight: 150.07 mg, dry weight: 98.64 mg) and rooting rate of plantlet (fresh weight: 2.17 g; dry weight: 0.09 g; leaf number: 20.33 leaves/plantlet) were also obtained under 7R + 3B condition.